Long-term Radiographic Results of Charnley Total Hip Arthroplasty for Osteoarthritis of the Hip—A Study of the Mechanism of Component Loosening - HIROSE, Shirou (Japanese Journal of Rheumatism and Joint Surgery, 1999)
Sixty-three Charnley total hip arthroplasties for the arthritic hip were reviewed to assess component loosening in a 10- to 23-year radiographic follow-up study. The mean age of patients at surgery was 60 years (38-76 years) . With radiographic evidence of definite loosening as the end point, the probability of survival of the acetabular component at 14 years after surgery was 70% in the first generation group using conventional surgical techniques and 94% in the second generation group using our improved surgical techniques. The probability of survival of the femoral component at 14 years was 90% and 94% in the first and the second generation group, respectively. Our present analysis of the first-generation cases suggests that the mechanism of early loosening is related to mechanical factor associated with insufficient cementing techniques. On the other hand, the mechanism of late loosening of the acetabular component is related to biological factor originating in wear particles.